2017
DOI: 10.1002/14651858.cd003633.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin type A therapy for cervical dystonia

Abstract: Botulinum toxin type A therapy for cervical dystonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 88 publications
2
50
0
7
Order By: Relevance
“…Die Therapie der motorischen Symptome beruht auf 2 Säulen [16]. Fokale Dystoni en sprechen meist gut auf Injektionen von Botulinumtoxin (BTX) A in die betroffene Muskulatur an [5,32,36]. Diese Therapie ist zeitintensiv und muss in speziellen Kursen oder Ambulanzen er lernt werden.…”
Section: Therapieunclassified
See 3 more Smart Citations
“…Die Therapie der motorischen Symptome beruht auf 2 Säulen [16]. Fokale Dystoni en sprechen meist gut auf Injektionen von Botulinumtoxin (BTX) A in die betroffene Muskulatur an [5,32,36]. Diese Therapie ist zeitintensiv und muss in speziellen Kursen oder Ambulanzen er lernt werden.…”
Section: Therapieunclassified
“…Auch multifokale oder segmentale Dystonien können mit BTX behandelt werden, wenn die eingesetzte Dosis und das Risiko für (systemische) Nebenwirkungen vertretbar sind. Beide Therapi en (BTX und THS) führen meist zu einer deutlichen Besserung der dystonen Symptome, einer Linderung der funktionellen Einschrän kungen und einer Verbesserung der Lebensqualität [5,19,23,32].…”
Section: Therapieunclassified
See 2 more Smart Citations
“…Botulinum toxin type A (BTX-A) is an exotoxin released by Gram-positive anaerobic Clostridium botulinum and has been widely used in the treatment of dystonia and in aesthetic field [14,15]. Clinical studies have confirmed that BTX-A can effectively relieve NP with mild adverse reactions [16,17].…”
Section: Introductionmentioning
confidence: 99%